Fatty Acid Profile, Component Calcium (Ca) and Organoleptic Test of Kaledo - Kundjae, Frilly K S; Gobel, Minarny; Rugayah, Nova (AgriSains, 2019)
Kaledo is a byproduct of cow, which is a leg bone that contains fat and calcium, but some people avoid kaledo fat for health reasons. The purpose of this study was to determine the profile of fatty acids, calcium (Ca) and the level of organoleptic preference of blackheads. This study consisted of 2 treatments and 3 replications (Ka = kaledo without the fat layer removed) and Kb = the layer of fat kaledo removed). The parameters observed were the profile of fatty acids, calcium (Ca) and organoleptic tests. The results showed the profile of Ka fatty acids consisted of SFA (butyrate, laurate, tridecanoate, myristate, pentadecanoate, palmitate, margarate, stearic, arachidate, heneicosanoate, and behenate), Kb did not have laurate and heneicosanoate; MUFA Ka (miristoleate, cis-10 pentadecanoate, palmitoleate, cis-10 heptadecanoate, oleate, cis-11 eicoceneoate, erucate, nervonate and elaidate), Kb does not have erukate and PUFA (linolelaidat, linoleat, linolenat, eikosadinoat, eikosatrinoat, EPA dan DHA). The average calcium Kb (0.35%) is higher than Ka (0.03%). Panelists like the same aroma, color, texture and taste as Kb. Cooling for 2 hours at 7ÂºC showed an increase in SFA (palmitate and stearate) and organoleptic quality similar to Ka. SFA is dominated by palmitate and stearate, MUFA is oleic and elaidate, PUFA is linoleic and EPA. The highest calcium Kb is still below the standard for total adult consumption. Panelists like all treatments of blackheads (Ka and Kb)